FUTURE-PROOF FOUNDATIONS: ADVANCED WATERPROOF TECHNIQUES FOR ANTI-SEEPAGE PROTECTION - Liu, Hui Min; Zhao, Yuan Qing (International Journal of Civil Engineering and Architecture and Real Estate, 2024)
The quality of buildings plays a pivotal role in the daily lives and safety of residents, while also significantly impacting urban development and the reputation of construction enterprises. Effective waterproofing and antiseepage construction are crucial measures to ensure construction quality. Persistent issues of building leakage have been a long-standing concern, potentially resulting in substantial losses if not addressed adequately. Additionally, substantial resources are invested in post-construction maintenance. Hence, ensuring a meticulous construction process to preempt leakage issues is of paramount importance.